A broken filter: Prefrontal functional connectivity abnormalities in schizophrenia during working memory interference - Anticevic, Alan (2012)
Characterizing working memory (WM) abnormalities represents a fundamental challenge in schizophrenia research given the impact of cognitive deficits on life outcome in patients. In prior work we demonstrated that dorsolateral prefrontal cortex (DLPFC) activation was related to successful distracter resistance during WM in healthy controls, but not in schizophrenia. Although understanding the impact of regional functional deficits is critical, functional connectivity abnormalities among nodes within WM networks may constitute a final common pathway for WM impairment. Therefore, this study tested the hypothesis that schizophrenia is associated with functional connectivity abnormalities within DLPFC networks during distraction conditions in WM. 28 patients and 24 controls completed a delayed non-verbal WM task that included transient visual distraction during the WM maintenance phase. We computed DLPFC whole-brain task-based functional connectivity (tb-fcMRI) specifically during the maintenance phase in the presence or absence of distraction. Results revealed that patients failed to modulate tb-fcMRI during distracter presentation in both cortical and sub-cortical regions. Specifically, controls demonstrated reductions in tb-fcMRI between DLPFC and the extended amygdala when distraction was present. Conversely, patients failed to demonstrate a change in coupling with the amygdala, but showed greater connectivity with medio-dorsal thalamus. While controls showed more positive coupling between DLPFC and other prefrontal cortical regions during distracter presentation, patients failed to exhibit such a modulation. Taken together, these findings support the notion that observed distracter resistance deficit involves a breakdown in coupling between DLPFC and distributed regions, encompassing both subcortical (thalamic/limbic) and control region connectivity.